2020
DOI: 10.1186/s12873-020-00384-1
|View full text |Cite
|
Sign up to set email alerts
|

Pre-hospital predictors of an adverse outcome among patients with dyspnoea as the main symptom assessed by pre-hospital emergency nurses - a retrospective observational study

Abstract: Background Dyspnoea is one of the most common reasons for patients contacting emergency medical services (EMS). Pre-hospital Emergency Nurses (PENs) are independently responsible for advanced care and to meet these patients individual needs. Patients with dyspnoea constitute a complex group, with multiple different final diagnoses and with a high risk of death. This study aimed to describe on-scene factors associated with an increased risk of a time-sensitive final diagnosis and the risk of dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 50 publications
2
11
0
Order By: Relevance
“…Two former emergency department studies that included patients with any complaint also found that decreased vigilance was an independent risk factor for 30-day mortality (3,18). The same conclusion was made in an EMS study of patients with the complaint of dyspnea (19). Two of these studies (3,19) similarly reported that low oxygen saturation was a risk factor for mortality.…”
Section: Hospital Mortality and The Search For Associated Predictorssupporting
confidence: 54%
See 1 more Smart Citation
“…Two former emergency department studies that included patients with any complaint also found that decreased vigilance was an independent risk factor for 30-day mortality (3,18). The same conclusion was made in an EMS study of patients with the complaint of dyspnea (19). Two of these studies (3,19) similarly reported that low oxygen saturation was a risk factor for mortality.…”
Section: Hospital Mortality and The Search For Associated Predictorssupporting
confidence: 54%
“…Two of these studies (3,19) similarly reported that low oxygen saturation was a risk factor for mortality. Patients with dyspnea have a higher risk of death with increasing age, which has also been shown by previous studies (9,19).…”
Section: Hospital Mortality and The Search For Associated Predictorsmentioning
confidence: 99%
“…Prior studies that assessed prehospital predictors of mortality demonstrated similar results: older age and low SBP [4][5][6][7][8][9][10] significantly increased mortality rates. In certain studies, increasing age [8] or low SBP [10] was indexed as part of an overall score of prehospital determinants that later was later used to assess mortality in the prehospital setting.…”
Section: Discussionmentioning
confidence: 75%
“…due to the unavailability of relevant data for the patients. However, a previous publication suggested that these variables are not associated with in-hospital delay but might be associated with pre-hospital delay and mortality [27]. Moreover, in terms of measuring the effect on the in-hospital delay rather than clinical outcomes, we adjusted for Killip classification, which is positively associated with medical history of patients [16,28] and could account for the partial confounding effect of medical history.…”
Section: Discussionmentioning
confidence: 99%